Microstructures and mechanical property of AlCoNiCrFe alloy annealed in high magnetic field. (August 2015) - Zhang, W. Q.; Lou, C. S.; Wu, X. C.; Fu, H. M.; Zhang, H. F.
<x content-type="archive" xml:space="preserve">Abstract</x> A rapidly solidified high entropy alloy AlCoNiCrFe was annealed at different temperatures with high magnetic field applied up to 4 T. Both precipitation and coarsening of the precipitates were promoted during annealing in a high magnetic field, and nanosized arrayed particles as well as boundary oriented secondary phases were formed with effects of magnetic field. The microstructural features were obtained owing to enhancement of atomic diffusion by applying high magnetic field. It was found that both hardness and yield strength were not strongly dependent on the magnetic field, but the ultimate compression strength is reduced as higher magnetic field is applied due to formation and coarsening of the precipitates on grain boundaries.